Pengaruh Luas Perpindahan Panas Kondensor Terhadap Volume Asap Cair Terkondensasi Hasil Pirolisis Tempurung Kelapa - Jamilatun, Siti; Nurkholis, Nurkholis (Universitas Ahmad Dahlan, 2016)
One of the products that can be made from coconut shell is making coconut shell carcoal by pyrolysis. In the pyrolysis process also produced liquid smoke, tar and uncondensed gasses. Liquid smoke is a byproduct of the activated charcoal industry has high economic value when compared with discharged into the atmosphere. Liquid smoke is a substance derived from the change of state to a liquid smoke, this process involves a change in the form of process heat transfer to the refrigerant fumes. Liquid smoke obtained simultaneously with the process of making charcoal (carbonization), smoke arising from incomplete combustion piped so that condensation will occur fluid droplets called liquid smoke. For coconut shell weight of 5 kg and 4 pipes condensor, the optimal volume of liquid smoke is 205 ml with a pyrolysis time 90 minutes and the theory of heat transfer surface area 0.076965 m2. For coconut shell weight of 5 kg and 8 pipes condensor, the optimal volume of liquid smoke is 215 ml with a pyrolysis time 90 minutes and the theory of heat transfer surface area 1.027437 m2. For coconut shell weight of 10 kg and 4 pipes condensor, the optimal volume of liquid is 183 ml with a pyrolysis time 300 minutes and the theory of heat transfer surface area 0.060404 m2. For 10 kg weight coconut shell and 8 pipes condensor, the optimal volume of liquid smoke is 205 ml with a pyrolysis time 210 minutes and the theory of heat transfer surface area 0.066801 m2.